Accurate investigation of coupled plasmonic resonances in a chain of silver nanowires - Stognii, N. P.; Sakhnenko, N. K. (IEEE, 2016)
This paper presents investigation of plasmonic properties of coupled metal nanowires arranged to form a finite linear chain. Coupled plasmon resonances of such structures embedded into dielectrics with different dielectric permittivity are studied. The main goals of the paper are to validate true potential of a plasmon nanowire-based structure in sensing applications and to reveal optimized configurations with narrowband plasmonic resonances and enhanced sensitivity.
Keywords: Plasma; localised surface plasmons; plasmon resonances; eigenfrequency; linear chain